2017
DOI: 10.1007/s12687-016-0291-3
|View full text |Cite
|
Sign up to set email alerts
|

Survey of family history taking and genetic testing in pediatric practice

Abstract: Family health history collection and genetic testing are core elements for the successful translation of genomics into primary care practice. Yet, little is known about how pediatric providers implement these elements in practice. We surveyed the membership of the American Academy of Pediatrics regarding family health history (FHH) collection and genetic testing in the primary care setting. Three hundred forty-nine (349) responses were analyzed with the initial response rate of 43.3%. Four principal findings w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 13 publications
1
43
0
Order By: Relevance
“…With the lack of a body of support, professional GPs may feel that the implementation of pharmacogenomics may not be optimal. Barriers to implementation identified under the main themes are not unique to General Practice (Saul et al 2017;McGrath and Ghersi 2016), and are also barriers to mainstreaming genomic practice among staff affiliated with primary care such as practice nurses (Brennan 2015) and pharmacists (Clemerson et al 2006;Haga et al 2016). However, the opportunities in implementation includes personalising medicine, to reduce toxicity, to enhance the efficacy of drugs and to use genome guided therapy in the setting of polypharmacy (Swinglehurst and Fudge 2017).…”
Section: Implications For Practicementioning
confidence: 99%
“…With the lack of a body of support, professional GPs may feel that the implementation of pharmacogenomics may not be optimal. Barriers to implementation identified under the main themes are not unique to General Practice (Saul et al 2017;McGrath and Ghersi 2016), and are also barriers to mainstreaming genomic practice among staff affiliated with primary care such as practice nurses (Brennan 2015) and pharmacists (Clemerson et al 2006;Haga et al 2016). However, the opportunities in implementation includes personalising medicine, to reduce toxicity, to enhance the efficacy of drugs and to use genome guided therapy in the setting of polypharmacy (Swinglehurst and Fudge 2017).…”
Section: Implications For Practicementioning
confidence: 99%
“…Five studies 3,8,11,17 included only physicians, while one study 10 included both physicians and advanced practice nurses. Study biases were addressed in the studies 5,8,10,11 that utilized self-reported surveys, namely, response bias and social desirability bias. Data collection procedures also varied among the studies with measurable outcomes, with 2 studies 10,17 employing semistructured interviews, another study 3 utilizing an online data collection program for quality improvement (QI) projects, and the remaining 3 studies 5,8,11 using nonvalidated, self-reported questionnaires developed by the researchers.…”
Section: Resultsmentioning
confidence: 99%
“…Family health history (FHH) has been identified as a clinical tool and was the first genetic test for clinicians. 5,6 FHH contains information about the health history of one’s biological relatives and can be used for risk assessment and screening, diagnostic evaluation, and disease management. The current gold standard for clinicians is to obtain a 3-generation family history.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the nature of provider specialty, ob-gyns are more likely to order BRCA 1/2 testing, whereas pediatricians are much less likely. A recent study also shows that most pediatric providers of the American Academy of Pediatrics are not comfortable in referring their patients to and consulting them about current genomic services [ 33 ]. Pediatric patients are an especially vulnerable population that involve a complex system of ethical, social, and legal issues when it comes to genomic testing.…”
Section: Discussionmentioning
confidence: 99%